1997
DOI: 10.3354/meps149105
|View full text |Cite
|
Sign up to set email alerts
|

Diel, seasonal and ontogenetic variations in the vertical distributions of four marine copepods

Abstract: Diel and seasonal v a n a t~o n s in the vertical distnbut~ons of Calanus finmarchicus Metrjd~a longa M lucens and C h~r~d l u s armatus in Malangen, northern Norway, were determined from F e b~ uary until December 1992 The vertical behav~our differed among the species and among the ditterent stages of a single species The vertical distnbution of C hnmarchlcus was d o m~n a t e d by seasonal rather than d~e l vertical migrat~on, and this species was found in surface waters during the spring phytoplankton bloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 20 publications
2
53
0
Order By: Relevance
“…We consider that this inaccuracy would not influence our sampling and would not affect results, because our study took place in spring when all the taxa that could possibly exhibit such a behaviour were higher in the water column as a result of seasonal ontogenetic migration towards the surface for reproduction. Recently, some studies revealed that vertical migration can occur in some taxa on much smaller amplitudes (Falkenhaug et al 1997). If this would be the case, our sampling design did not allow us to detect such a behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…We consider that this inaccuracy would not influence our sampling and would not affect results, because our study took place in spring when all the taxa that could possibly exhibit such a behaviour were higher in the water column as a result of seasonal ontogenetic migration towards the surface for reproduction. Recently, some studies revealed that vertical migration can occur in some taxa on much smaller amplitudes (Falkenhaug et al 1997). If this would be the case, our sampling design did not allow us to detect such a behaviour.…”
Section: Discussionmentioning
confidence: 65%
“…Because vertical positioning within the upper water can have large effects on drift trajectories (67), we released particles at three different depths. However, although C. finmarchicus is mainly confined to the upper 50 m in spring, older stages (CIV-CVI) might have a deeper distribution, in particular after June when descent to overwintering begins (68). Focusing on the upper water layer might underestimate observed biomass in the statistical analysis, in particular toward the end of the summer survey.…”
Section: Methodsmentioning
confidence: 96%
“…Ontogenic differences in DVM have been previously reported for C. pacificus in mesocosm experiments (Huntley & Brooks 1982) and in the field (Osgood & Frost 1994), C. finmarchicus in Scottish lochs and the Norwegian Sea (Nicholls 1933, Marshall & Orr 1955, Dale & Kaartvedt 2000, Metridia lucens in different areas (Osgood & Frost 1994, Hays et al 1995, Falkenhaugh et al 1997, Timonen 1997, and for Neocalanus gracilis, Pleuromamma abdominalis and Euchaeta acuta in the Mediterranean (Andersen et al 2001).…”
Section: Discussionmentioning
confidence: 99%